Covalent organic polymer assisted synthesis of bimetallic electrocatalysts with multicomponent active dopants for efficient oxygen evolution reaction. (20th October 2019) - Ma, Dong-Dong; Cao, Changsheng; Li, Xiaofang; Cheng, Jin-Tian; Zhou, Li-Li; Wu, Xin-Tao; Zhu, Qi-Long
Abstract: The development of highly active and stable electrocatalysts for the oxygen evolution reaction is of great importance for renewable-energy. Herein, a novel hybrid nanomaterial with multicomponent active dopants was conveniently fabricated by pyrolytic conversion from a bimetallic ion-decorated heteroatom-rich (P, S and N) covalent organic polymer (COP) composite. The unique nanostructure with innumerable Co9- x Ni x S8 and CoNiP nanoparticles anchored on P/S/N multi-doped carbon/carbon nanotubes, through in situ electrochemical reconstruction effectively provides substantial active sites and promotes charge transfer, and hence affords outstanding activity with a low overpotential of 270 mV at 10 mA cm −2 and excellent stability for oxygen evolution reaction based on two runs of 10-h durability test in alkaline solution, which much outperformed the fewer-component counterparts. Graphical abstract: Image 1 Highlights: A new heteroatom-rich (P, S and N) covalent organic polymer was designed and synthesized. P/S/N multi-doped carbon/carbon nanotubes anchored with Co9- x Ni x S8 and CoNiP nanoparticles was fabricated. The optimized catalyst showed efficient and long-term stable electrocatalytic oxygen evolution.